2017
DOI: 10.1080/09613218.2017.1304095
|View full text |Cite
|
Sign up to set email alerts
|

The role of lobbies: short-term thermal transitions

Abstract: Maintaining comfort levels while reducing energy demand in buildings in the face of climate change is a key challenge in temperate zones. Creating transitional spaces and thermal variation in buildings may offer a way forward. This paper is a study of seasonal short-term thermal transitions in the lobby areas of three higher education buildings in Sheffield, UK involving 1,749 participants, thermal comfort questionnaires and simultaneous climatic measurements. New patterns of thermal transitions were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Overall, due to the huge power consumption for space heating in the UK educational buildings [8] combined with the considerable influence of thermal comfort on students' productivity in academic environments [13,61], several studies have been conducted to evaluate the thermal environment in the UK higher educational buildings [10,[62][63][64][65][66]. However, none of these studies has taken into account the different climatic conditions over the UK.…”
Section: Research Aim and Outputmentioning
confidence: 99%
“…Overall, due to the huge power consumption for space heating in the UK educational buildings [8] combined with the considerable influence of thermal comfort on students' productivity in academic environments [13,61], several studies have been conducted to evaluate the thermal environment in the UK higher educational buildings [10,[62][63][64][65][66]. However, none of these studies has taken into account the different climatic conditions over the UK.…”
Section: Research Aim and Outputmentioning
confidence: 99%
“…38 Research suggests that it is possible to positively alter thermal perception through the judicious use of transition spaces, reversing the negative effects of air conditioning. 39 The historic precedents explored in this paper demonstrate that environmental diversity not only offers improved opportunities for thermal comfort and adaptation compared with mechanically controlled interiors, but can also enhance our perceptions and experience of the architectural environment. Furthermore, the spatial cost of these spaces can be offset by the flexibility they offer for informal meetings, gatherings, and events, and the financial and energy savings to be made through a reduction in the scale and specification of HVAC equipment.…”
Section: Discussionmentioning
confidence: 88%
“…Numerous studies have shown that IEQ is an important part of the indoor environment that has a great influence on the comfort of building occupants and enhances their QOL (Vargas & Lawrence, 2017;Altomonte & Schiavon, 2013;Garre-Olmo et al, 2012;Frontczak & Wargocki, 2011). The IEQ is related to the acoustic, lighting, and thermal environments, and the indoor air quality (Feng et al, 2018;Garre-Olmo et al, 2012;Frontczak & Wargocki, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%